Summary Proceedings of the Thirty-Fifth Annual Meetings of the Board of Governors, 1980. (Summary Proceedings; 35th Annual Meeting, 1980, 1980)
The speeches made by officials attending the IMF-World Bank Annual Meetings are published in this volume, along with the press communiques issued by the International Monetary and Financial Committee and the Development Committee at the conclusion of the meetings.